Gibel carp population and its parasites in Madatapa Lake (South Georgia) - Bella Japoshvili; Levan Mumladze (Frontiers in Marine Science, 2015)
Madatapa Lake is an oligotrophic lake located in Javakheti plateau (Southern Georgia) at 2108 m a.s.l. and is the part of the Javakheti Protected Areas since 2011. The lake have a natural volcanic origin with a surface area of 8.8 km2 and with a maximum depth of 1.7 m. The lake is historically known to be free of fish species which is believed to be a result of severe winter conditions. After the middle 90th the gibel carp [Carassius gibelio (Bloch, 1782)] was firstly appeared there. However the exact date and the source of invasion of gibel carp in the lake is unknown and currently untraceable. While gibel carp is a very successful invasive fish species in Georgian inland waters, very limited data is available on its biology, ecology and even distribution as well as its ecological impacts and economic importance in the region. For the first time, we studied the population characteristics of gibel carp in Lake Madatapa (South Georgia) with the aim to reveal the extent of its morphological variability, sex ratio, length-weight relationship and its parasitic community. One hundred and forty one individuals presented a mean weight 37.5 g (SD=53, range [13.3-471.7]) and average length of 12.5 cm (SD=2.9, range[9.4-30]). The number of lateral line scales and gill rakers varied between 29-31, and 36-47, respectively. Sex was determined in 105 specimens (the gonads of remaining specimens were either strongly damaged by the parasites or were not developed) and the sex ratio was significantly female biased (1/1.8, Chi-square test p<0.01). There is no size or weight differences between males and females (t-test, p<0.05 for both cases). Overall length-weight relationship was within the published data. There is no significant difference (p>0.05) between the regression coefficients for males and females and the slope (b) do not differ significantly from 3. A sub-sample of thirty four individuals were examined for parasitic infections and 91% (31) were infected with one or two parasites. The plerocercoids of cestoda (Ligula intestinalis L., 1758) had highest prevalence (75%), whereas only 38% of studied fishes were infected with metacercariae of digenean trematode (Diplostomum spathaceum Rud., 1819). Both parasites were detected in only 9 specimens (27%). Cestodes were found in 5 female whereas sex was not determined for other 8 specimens. In 29 specimens infected with L. intestinalis, 24 (83%) had completely degenerate gonads. From other remaining five specimens for which the sex were determined, only one was the male. In the three specimens without parasites two were females. Since we are not able to infer the difference in parasitism intensity between sexes directly, the healthy specimens have indistinguishable sex ratio as an overall population (Chi-square test p>0.05).